2021
DOI: 10.1002/admt.202000984
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh Sensitivity Flexible Pressure Sensors Based on 3D‐Printed Hollow Microstructures for Electronic Skins

Abstract: Here, ultrahigh sensitivity flexible pressure sensors comprised of 3D‐printing flexible hollow microstructure substrates, gold film spray‐coated on the substrates, and Ag interdigital electrodes are reported. The finite element analysis (FEA) shows that the hollow microcylinder structure has better compression performance compared to solid microcylinder structure. Diverse solid and hollow microstructures, such as microcylinder, microsawtooth, and microrectangle structures are built to investigate the performan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(33 citation statements)
references
References 50 publications
0
33
0
Order By: Relevance
“…The one-pot multimaterial 3D printing process enables the integration of various functional inks into the 3D sensor and provides a conformal design and high performance. For the 3D printing method, non-conductive polymer material is usually used for backbone structuring, and successive post processing is needed to add the conductive layer for their application in electronic devices [ 260 ]. Xia et al reported a flexible piezoresistive sensor based on 3D-printing and spray-coating [ 260 ].…”
Section: Microstructure Fabrication Strategies Of Pressure Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…The one-pot multimaterial 3D printing process enables the integration of various functional inks into the 3D sensor and provides a conformal design and high performance. For the 3D printing method, non-conductive polymer material is usually used for backbone structuring, and successive post processing is needed to add the conductive layer for their application in electronic devices [ 260 ]. Xia et al reported a flexible piezoresistive sensor based on 3D-printing and spray-coating [ 260 ].…”
Section: Microstructure Fabrication Strategies Of Pressure Sensorsmentioning
confidence: 99%
“…For the 3D printing method, non-conductive polymer material is usually used for backbone structuring, and successive post processing is needed to add the conductive layer for their application in electronic devices [ 260 ]. Xia et al reported a flexible piezoresistive sensor based on 3D-printing and spray-coating [ 260 ]. A hollow microcylinder structure flexible substrates is firstly fabricated by 3D-printing using photosensitive resin, and then, Au nanoparticles were spray-coated on the microstructured substrates to form the sensing layer.…”
Section: Microstructure Fabrication Strategies Of Pressure Sensorsmentioning
confidence: 99%
“…Similarly, Xia et al reported 3D printed microstructures with gold nanoparticles for the flexible pressure sensors, for electronic skins. [39] In their work, by taking the advantage of an expensive stereolithography printer, they employed a bottomup fabrication process, and a microcylinder structure of flexible substrate was fabricated. Yet, not enough effort was spared in the combination of the structured layer formation and device fabrication to enable rapid, consistent, and cost-effective fabrication of sensitive, reliable, stable, and cost-effective wearable and flexible bioelectronic wearable sensors.…”
Section: Introductionmentioning
confidence: 99%
“…where ΔR and ΔP are the relative resistance change and the pressure change respectively, and R 0 represents the initial resistance. 16 3. RESULTS AND DISCUSSION 3.1.…”
Section: Methodsmentioning
confidence: 99%